The narratives of women in South Africa who use social media to talk about gender-based violence - Walton, Donica Jasmin (Rhodes University, Faculty of Humanities, Department of Psychology)
There has been research conducted, both globally and in South Africa, on social media activism against gender-based violence (GBV). However, most research on the topic is based on participants in other parts of the world. Not much has been published on Black, African women. More specifically, not much is known about how women in South Africa experience using social media to talk about GBV. This research project draws on critical feminism and a narrative-discursive approach to explore the narratives of women in South Africa who use social media to talk about GBV. This is done by identifying the discourses women draw on to construct narratives, the subject positions utilised within these discourses, and how "trouble" and "repair" features in the narratives and positioning of women. Twelve interviews were conducted with women who volunteered and fit the inclusion criteria. The analysis of data was presented in two parts. The first set of discourses (discourses of 'efficacy', 'convenience', and 'education') were focused on what the use of social media achieves irrespective of the topic being discussed. These discourses speak to the idea that social media is powerful and useful because of its reach, speed, immediacy, and ability to be used to educate and be educated. The second set of discourses (discourses of 'community and solidarity', 'validation', and 'vulnerability') were focused on what the use of social media does for the people participating. Women have found a community and solidarity, and their experiences and thoughts have been validated on social media. Overall, the women in this research project justified their use of social media for activism against GBV, and acknowledged the tension that exists because despite its potential, there are limitations.
Keywords: Women -- Violence against -- South Africa; Social media and society -- South Africa; Internet and activism -- South Africa; Discourse analysis, Narrative; Internet and women -- South Africa; Subject positions